CAN HISTORICAL SITES IN MANADO BE AN EDUCATIONAL TOURIST ATTRACTION? - Dimas Ero Permana; Benny Irwan Towoliu; Agustinus Lumettu; Jufrina Mandulangi (Sanata Dharma University, 2020)
Manado as the capital of North Sulawesi province in the past four years has become one of the leading destinations for Chinese tourists visiting Indonesia. One of the things that has not yet been explored well is cultural and historical tourism. Though this can be a special attraction when managed properly, it can be an alternative to tourism other than marine tourism. But in his observation the sites were not used as a means of learning culture and history for the people of Manado. The purpose of this study is the use of Historical Sites as Educational Tourism. The analytical method used is descriptive by combining qualitative and quantitative methods. The research instruments used were interviews, observation and questionnaires. The analytical method used is the assessment using a Likert attitude scale. The results showed that the Manado community agreed that the various sites were used as educational tourism